2020
DOI: 10.1080/07391102.2020.1831610
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine focused covalent inhibitors against the main protease of SARS-CoV-2

Abstract: In viral replication and transcription, the main protease (Mpro) of SARS-CoV-2 plays an important role and appears to be a vital target for drug design. In Mpro, there is a Cys-His catalytic dyad, and ligands that interact with the Cys145 assumed to be an effective approach to inhibit the Mpro. In this study, approximately 1400 cysteine-focused ligands were screened to identify the best candidates that can act as potent inhibitors against Mpro. Our results show that the selected ligands strongly interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The first comprises peptidomimetics designed to covalently interact with Cys145 in the catalytic site that share four features: a) moderate size; b) a group mimicking a glutamine side chain; c) a branched lipophilic group; d) a reactive electrophilic ‘warhead’, such as aldehydes, Michael acceptors, and epoxy ketones responsible for the covalent bond [ 25 , 26 ]. However, the possibility of non-specific biological interactions due to their huge reactivity, must be considered for the subsequent in vivo evaluation of this type of inhibitors [ 27 , 28 ]. Accordingly, the less reactive non-covalent inhibitors may represent safer antiviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…The first comprises peptidomimetics designed to covalently interact with Cys145 in the catalytic site that share four features: a) moderate size; b) a group mimicking a glutamine side chain; c) a branched lipophilic group; d) a reactive electrophilic ‘warhead’, such as aldehydes, Michael acceptors, and epoxy ketones responsible for the covalent bond [ 25 , 26 ]. However, the possibility of non-specific biological interactions due to their huge reactivity, must be considered for the subsequent in vivo evaluation of this type of inhibitors [ 27 , 28 ]. Accordingly, the less reactive non-covalent inhibitors may represent safer antiviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…(Pillaiyar, et al, 2020) While classical docking studies are widely reported in the literature,( Kitchen et al, 2004 ) docking studies for covalent protein inhibition are less common,( Kumalo et al, 2015 ; Sotriffer, 2018 ) in particular with SARS-CoV-2 main protease. ( Liu et al, 2020 ; Paul et al, 2020 ) Despite covalent inhibition approaches are less studied because the requirement of a nucleophilic residue is a structural limitation and they can be considered as harmful, the resurgence of covalent drugs encourage to also consider covalent inhibition. ( Dalton and Campos, 2020 ; Ghosh et al, 2019 ; Singh et al, 2011 ) Irreversible specific protein inhibitors are now reported, such as in the case of the Ras protein possessing a G12C mutation, a promising example of potential anticancer strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vivo studies of these ligands can only yield their true efficacy against M pro . Similarly, several covalent inhibitors, such as ketone-based covalent inhibitors [69] , cysteine focussed covalent inhibitors [70] , etc. were proposed for the inhibition of M pro .…”
Section: Drug Targets Of the Main Protease (M Promentioning
confidence: 99%